Studi Aktivitas Sosial dan Ekonomi Masyarakat Wilayah Pesisir di Kabupaten Wakatobi - Fyka, Samsul Alam (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2017)
Social and economic living conditions of coastal communities in Wakatobi is very dependent on the season because the bulk of coastal communities in Wakatobi still have facilities relatively traditional fishery and very limited. The purpose of this study were (1) to know the social and economic activities of coastal areas in Wakatobi. (2) determine household income of coastal communities in Wakatobi. Data collected through direct surveys, conduct focus group discussions, questionnaires and data analysis. Data were analyzed by qualitative analysis and the analysis of household income. The results of the study are socio-economic activities of coastal communities around the coastal area is very diverse, ranging from farmers (gardening), merchants, and fishermen. But of all the types of people the main activity in coastal areas as fishermen work very dominating. While household income of fishermen very fluctuate with the change of seasons. Average income in the strong wave season is Rp. 1,236,233, - and increased to Rp. 1,427,422, - increased revenue continues to occur when a weak season surge to Rp. 1.606.010, -.